Baseline titre of Widal amongst healthy blood donors at tertiary care hospital - Khorgade, Ranjana R.; Bhise, Pramod R. (International Journal of Research in Medical Sciences, 2017)
Background: Indian subcontinent is a hotspot of Typhoid activity with high prevalence rates. The Widal test is one of the commonly used sero-diagnostic test for typhoid fever in developing countries. Lack of proper knowledge of baseline titre of Widal test can lead to over diagnosis of typhoid fever leading to mismanagement of patients. A single cut off value on average titre among healthy individuals needs to be determined. So, the purpose of the present study was to develop recommendations for the interpretation of Widal test results in the local region. The objectives were to determine the baseline Widal titre of study population and to propose titre-values of significance in the diagnosis of enteric fever. Methods: Sera of 242 apparently healthy blood donors from January 2016 to December 2016 in blood bank and Department of Microbiology, Dr. PDMMC, Amravati, Maharashtra, India were subjected to standard quantitative tube and semi-quantitative slide Widal test to know the titre. Results: Highest titre obtained by tube Widal test for TO was 1:320, for TH- 1:160, for AH- 1:80, and for BH- 1:80. Tube Widal titres of ≤1:160 for TO were seen in 238 (98.34%) and for TH titre of ≤1:80 were seen in 238 (98.34%), TO and TH titres of ≥1:160 were seen in 24 (9.91%) and 4 (1.65%) respectively. TO titre of 1:320 was seen in 4(1.65%) and TH titre of 1:160 was seen in 4 (1.64%). Highest titre obtained by semi-quantitative slide Widal for TO was 1:640, for TH, AH and BH was 1:160. Conclusions: We recommend that TO titre of ≥1:320 and TH titre ≥1:160 as diagnostic of typhoid fever and for AH and BH, titres of ≥1:80 should be considered diagnostic respectively in our region. Because of high expected false positivity rate of slide Widal test.